Pharmacokinetics of Sofosbuvir/Velpatasvir and efficacy of an alternate‐day treatment in hemodialysis patients with chronic hepatitis C infection - Pajaree Chariyavilaskul; Nantaporn Prompila; Supeecha Wittayalertpanya; Sookruethai Lekhyananda; Wisit Prasithsirikul; Thananda Trakarnvanich; Somboon Jeenapongsa; Paweena Susantitaphong; Stephen Kerr; Anchalee Avihingsanon; Pisit Tangkijvanich; Kearkiat Praditpornsilpa (Wiley, 2024)
Abstract Sofosbuvir/Velpatasvir (SOF/VEL) is a combination drug used for chronic hepatitis C (HCV) infection. However, limited information exists regarding the pharmacokinetics of SOF/VEL and its metabolites in hemodialysis patients. We conducted a prospective investigation of the pharmacokinetic parameters of SOF/VEL after a single dose of SOF/VEL (400/100 mg) on days with and without dialysis in 12 Thai hemodialysis patients with chronic HCV infection, who had been undergoing hemodialysis for a duration of 0.5-20 years. Blood samples were collected before dose (0) and 0.5, 1.0, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, 8.0, and 12.0 h after dose. Dialysate samples were also collected before dose (0) and 1.0, 2.0, 3.0, and 4.0 h after dose. Plasma and dialysate samples were quantified for SOF and its metabolite, GS‐331007, and VEL concentrations using a fully validated LCMS technique. In addition, a preliminary efficacy study was conducted using the proposed SOF/VEL dose reduction regimen in all patients. No differences in SOF/VEL PK parameters between on‐ and off‐dialysis studies. On the contrary, GS‐331007 exhibited a 30% reduction in the area under the plasma concentration-time curve from time 0 to 24 h (AUC0‐24h) on dialysis days compared with non‐dialysis days (AUC0‐24h ratio 0.68 vs. 1.04, respectively). The dialysis clearance of SOF and GS‐331007 was 9.35 (8.72-15.11) and 8.89 (8.52-14.07) mL/min, respectively. Subsequently, an alternate‐day regimen of SOF/VEL (400/100 mg) was administered for 12 weeks, resulting in an undetectable plasma HCV viral load without side effects. Further clinical studies are warranted to validate the efficacy and safety of our proposed dose reduction regimen.